OP90 The embodiment of gender divisions of labour: gender divisions of labour and inflammatory markers in the uk household longitudinal study. (2nd September 2017) - McMunn, A; Bird, L; Webb, E; Sacker, A
Abstract : Background: While the gender division in paid work has progressively diminished, this is less true of unpaid labour. A gender perspective requires an extension of investigations of stress and health beyond paid work to include unpaid labour. This study investigates associations between gender divisions of 'total labour' and inflammatory markers thought to potentially link chronic stress exposure with disease outcomes amongst contemporary UK couples. Methods: The study sample includes co-resident, opposite sex couples aged 16–65 in Wave 2 of the UK Household Longitudinal Study or Understanding Society. Gender divisions of labour were measured using the number of weekly hours that each member of the couple spent in paid work, housework, and caring, as well as who has responsibility for children. Inflammatory marker outcomes included C-Reactive Protein (CRP) and fibrinogen. High CRP was defined as greater than 3 mg/L. Cross-sectional multivariate regression models were used to investigate associations between gender divisions in paid work, caring, housework and childcare with inflammatory markers, adjusting for household income, educational qualifications, longstanding illness and age, stratifying by gender to investigate whether associations are differential within couples. Results: Gender divisions of labour were associated with raised inflammation for men but not women. Men living in households in which women were providing care to an adult or doing all of the housework had significantly higher levels of Fibrinogen (caring: coef=0.11, 95% CI=0.04–0.19; housework: 0.08, 0.02–0.14) and CRP (caring: OR=1.66, 95% CI=1.15–2.39; housework: OR=1.50, 1.06–2.14) compared with men in households in which neither partner provided care or both did few hours of housework. In addition, men in traditional 'male breadwinner' households, or childless households, were significantly less likely to have raised CRP levels (paid work: OR=0.49, 0.36–0.68; parental status: 0.64, 0.44–0.92) than men in dual-earner households or those in which childcare was equally shared between parents. Conclusion: Contrary to expectations, inflammatory markers were significantly associated with gender divisions of labour within couples for men and not for women. While potential stress-reducing benefits of participation in paid work and childlessness are aligned with prior research, further investigation is required to better understand the effects of women's caring and housework on men's inflammation. Next steps include investigation of the identity of care recipients, non-linear associations with hours spent in housework, and interaction effects between labour types.